Application of the optically stimulated luminescence (OSL) technique for mouse dosimetry in micro‐CT imaging. Issue 12 (15th November 2013) - Vrigneaud, Jean‐Marc; Courteau, Alan; Ranouil, Julien; Morgand, Loïc; Raguin, Olivier; Walker, Paul; Oudot, Alexandra; Collin, Bertrand; Brunotte, François
Abstract : Purpose: : Micro‐CT is considered to be a powerful tool to investigate various models of disease on anesthetized animals. In longitudinal studies, the radiation dose delivered by the micro‐CT to the same animal is a major concern as it could potentially induce spurious effects in experimental results. Optically stimulated luminescence dosimeters (OSLDs) are a relatively new kind of detector used in radiation dosimetry for medical applications. The aim of this work was to assess the dose delivered by the CT component of a micro‐SPECT (single‐photon emission computed tomography)/CT camera during a typical whole‐body mouse study, using commercially available OSLDs based on Al2 O3 :C crystals. Methods: : CTDI (computed tomography dose index) was measured in micro‐CT with a properly calibrated pencil ionization chamber using a rat‐like phantom (60 mm in diameter) and a mouse‐like phantom (30 mm in diameter). OSLDs were checked for reproducibility and linearity in the range of doses delivered by the micro‐CT. Dose measurements obtained with OSLDs were compared to those of the ionization chamber to correct for the radiation quality dependence of OSLDs in the low‐kV range. Doses to tissue were then investigated in phantoms and cadavers. A 30 mm diameter phantom, specifically designed to insert OSLDs, was used to assess radiation dose over a typical whole‐body mouse imaging study. Eighteen healthy female BALB/c mice weighing 27.1 ± 0.8 g (1 SD) were euthanized for small animal measurements. OLSDs were placed externally or implanted internally in nine different locations by an experienced animal technician. Five commonly used micro‐CT protocols were investigated. Results: : CTDI measurements were between 78.0 ± 2.1 and 110.7 ± 3.0 mGy for the rat‐like phantom and between 169.3 ± 4.6 and 203.6 ± 5.5 mGy for the mouse‐like phantom. On average, the displayed CTDI at the operator console was underestimated by 1.19 for the rat‐like phantom and 2.36 for the mouse‐like phantom. OSLDs exhibited a reproducibility of 2.4% and good linearity was found between 60 and 450 mGy. The energy scaling factor was calculated to be between 1.80 ± 0.16 and 1.86 ± 0.16, depending on protocol used. In phantoms, mean doses to tissue over a whole‐body CT examination were ranging from 186.4 ± 7.6 to 234.9 ± 7.1 mGy. In mice, mean doses to tissue in the mouse trunk (thorax, abdomen, pelvis, and flanks) were between 213.0 ± 17.0 and 251.2 ± 13.4 mGy. Skin doses (3 OSLDs) were much higher with average doses between 350.6 ± 25.3 and 432.5 ± 34.1 mGy. The dose delivered during a topogram was found to be below 10 mGy. Use of the multimouse bed of the system gave a significantly 20%–40% lower dose per animal ( p < 0.05). Conclusions: : Absorbed doses in micro‐CT were found to be relatively high. In micro‐SPECT/CT imaging, the micro‐CT unit is mainly used to produce a localization frame. As a result, users should pay attention to adjustable CT parameters so as to minimize the radiation dose and avoid any adverse radiation effects which may interfere with biological parameters studied.